2009
DOI: 10.1080/13600800903191955
|View full text |Cite
|
Sign up to set email alerts
|

Of what benefit and to whom? Linking Australian humanities research with its ‘end users’

Abstract: There is increasing pressure for university researchers to secure 'end-user' support for their research projects. Yet the ways in which this imperative affects humanities researchers, operating in a science-centric funding environment, have not yet been fully explored. This paper presents the findings of an empirical study into the experiences of humanities researchers in securing competitive national funding for research involving collaborations with the private and public sector. It also provides quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…Consequently, it seems that humanities have only just begun to realize the need for explicitly articulating social relevance of their research. Pitman and Berman (2009) find in a study of research applications that only a small portion of humanities applicants explicitly identified social or economic benefits of their research. When prospected benefits were included, they were primarily identified as cultural (in the form of knowing more about a cultural phenomenon).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it seems that humanities have only just begun to realize the need for explicitly articulating social relevance of their research. Pitman and Berman (2009) find in a study of research applications that only a small portion of humanities applicants explicitly identified social or economic benefits of their research. When prospected benefits were included, they were primarily identified as cultural (in the form of knowing more about a cultural phenomenon).…”
Section: Introductionmentioning
confidence: 99%
“…Second, this partnership is also drawing upon many of the factors that contribute to project success. These include open communication and commitment to the project, as well as some prior experience working together (Barnes, Pashby & Gibbons 2002;Phillips 2009;Pitman and Berman 2009;Plewa et al 2013), which flows both from the earlier INKE project and by virtue of already spending more than three years in discussion about the project, its research question, and methods for both undertaking the work and ways to collaborate. It appears that the right people from the right organizations are in place, for these partnerships are grounded in relationships (Phillips 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As university and industry members work through the partnership process, a combination of factors exist that influence success (Phillips 2009;Barnes, Pashby & Gibbons 2002). Some universal factors include open communication and trust, both of which can take time to develop, commitment to the project and to outcomes where mutual benefits exists for both parties, and prior experience working together (Barnes, Pashby & Gibbons 2002;Phillips 2009;Plewa et al 2013: Pitman andBerman 2009). Ultimately, the basis for a partnership that meets the needs of both parties is a relationship with the right people in place; all must play a role articulating and agreeing upon goals and outcomes (Phillips 2009).…”
Section: Success Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversy over what is regarded as valid knowledge, the most reliable ways of knowing and the basis upon which some types of knowledge are accorded respectability and positions of influence more than others, in the process of deciding what is 'good' and 'bad' for society, is nothing new (Pitman & Berman, 2009;Snow, 1965;Wilson, 2008). Debate about whether the social sciences and humanities can be scientific in the same way as the physical sciences has also persisted for some time.…”
Section: Introductionmentioning
confidence: 99%